A Multilevel Domain Decomposition Approach for Studying Coupled Flow Applications (Communications in Computational Physics, 2018)
In this paper, a multilevel domain decomposition approach based on multigridmethods for obtaining fast solutions for coupled engineering flow applicationsarising on complex domains is presented. The proposed technique not only allowssolutions to be computed efficiently at the element level but also helps us to achieveproper accuracy, load balancing and computational efficiency. Numerical results presenteddemonstrate the robustness of the proposed technique.